2020
DOI: 10.1093/jjco/hyaa086
|View full text |Cite
|
Sign up to set email alerts
|

Understanding help-seeking behaviour in relation to psychosocial support services among Japanese cancer patients

Abstract: Background There are various psychosocial support services for cancer patients in Japan; however, their utilization rate is lower than in Western countries. The aim of this study was to investigate the actual status of the utilization of such services and the related factors of their use, using the transtheoretical model. Methods We conducted an Internet survey of cancer outpatients. They were asked for information on their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…1,18 When medical staff makes recommendations to patients for use, it is expected that communication would be performed based on factors affecting HSB of each stage and the characteristics of the stages. 33 This same framework is also important when developing an intervention promoting the utilization of psychosocial support services among cancer patients, such as by creating posters and flyers or establishing a promoting system. That is, such factors and the characteristics of the stages were expected to be considered rather than addressing everyone in the same way.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,18 When medical staff makes recommendations to patients for use, it is expected that communication would be performed based on factors affecting HSB of each stage and the characteristics of the stages. 33 This same framework is also important when developing an intervention promoting the utilization of psychosocial support services among cancer patients, such as by creating posters and flyers or establishing a promoting system. That is, such factors and the characteristics of the stages were expected to be considered rather than addressing everyone in the same way.…”
Section: Discussionmentioning
confidence: 99%
“…This study found more users of psychosocial support services in the Contemplation than in the Precontemplation stages. As an individual moves from one stage to another according to TTM, 28 and high awareness of the problem is an important factor of HSB, than the other stages, 33 and, as high extroversion leads to active and adaptive coping, 34,35 these participants might have been able to use services as needed.…”
Section: Relationship Between Stage At Time 1 and Use At Timementioning
confidence: 99%
See 3 more Smart Citations